If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5.2b + 4.6 = 7.72 Reorder the terms: 4.6 + 5.2b = 7.72 Solving 4.6 + 5.2b = 7.72 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4.6' to each side of the equation. 4.6 + -4.6 + 5.2b = 7.72 + -4.6 Combine like terms: 4.6 + -4.6 = 0.0 0.0 + 5.2b = 7.72 + -4.6 5.2b = 7.72 + -4.6 Combine like terms: 7.72 + -4.6 = 3.12 5.2b = 3.12 Divide each side by '5.2'. b = 0.6 Simplifying b = 0.6
| 4t^2-25t+28=0 | | 3x+3y-2x-2= | | (2x-6)(9x+1)=0 | | 5x^4+2x^3=10x^7 | | x^2-3x=1.8 | | 9y^2+z^2=16 | | 4x+x+3x+8x= | | 3(2x-6)=2(6x-3) | | An=xy | | -144/=-16 | | 3.67-6.7x+1.11=22.2 | | -(6xy-10)+2(5xy+8)= | | 5x+6x-3x-5=51 | | (4x^3+4x^2-3x)(x^2-7)=0 | | 5+(3x-3)=3x-(8x-6) | | C-50=28 | | 23=u-10 | | x(3x+2)=8 | | 30x^2-1=5x^2-1 | | x4=1/10 | | 6/7s-5/6s=4/21 | | 15=c/5 | | M+7m+3m-6= | | 2cos^2(2x)-cos(x)=0 | | 2s^2+3s-1=0 | | x^4-y^4-3y^2+1=0 | | -16x^2+75x-51=0 | | -6z=15-7z | | 2cos^2(2x)-cos(2)=0 | | 2x-3(x+3)=23 | | 4k-8=5(k+7) | | 25,200/525 |